2007
DOI: 10.1539/joh.49.453
|View full text |Cite
|
Sign up to set email alerts
|

Development of Japanese Version of the Checklist Individual Strength Questionnaire in a Working Population

Abstract: Development of Japanese Version of the Checklist Individual Strength Questionnaire in a Working Population: Yutaka Aratake, et al. Department of Occupational Mental Healthl, Graduate School of Medical Sciences, Kitasato University—The aims of the present study were to develop and validate the Japanese version of the checklist individual strength questionnaire (CIS) which is used to measure prolonged fatigue not only in the general population but also in the working population. We obtained permission to use CIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…A total CIS score of over 76 has been shown to be related to a tendency to take sick leave and for work disability 19,24) . The mean CIS score in this study was 76.7 (SD=18.4) for men and 80.8 (SD=17.4) for women; this may suggest that the sample in the present study, namely teachers replying to our questionnaire, showed a higher prolonged fatigue level compared with the overall population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total CIS score of over 76 has been shown to be related to a tendency to take sick leave and for work disability 19,24) . The mean CIS score in this study was 76.7 (SD=18.4) for men and 80.8 (SD=17.4) for women; this may suggest that the sample in the present study, namely teachers replying to our questionnaire, showed a higher prolonged fatigue level compared with the overall population.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese version of the checklist individual strength (CIS) questionnaire was used to measure prolonged fatigue 18,19) . The CIS has four subscales (subjective feeling of fatigue, concentration, motivation, and physical activity) and consists of 20 questions.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were instructed to note their selfassessment of night sleep for day-shift days on the following morning. Fatigue was assessed using the Checklist Individual Strength (CIS) questionnaire 28,29) .…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The Japanese version of the checklist has been shown to be satisfactorily reliable and valid for assessing fatigue among a Japanese population 30,31) . The CIS is a questionnaire about fatigue developed by Vercoulen et al that is widely used all over the world.…”
Section: Fatiguementioning
confidence: 99%